Air temperature recordings in infant incubators. Issue 3 (March 1975) - Aynsley-Green, A; Roberton, N R; Rolfe, P
Abstract : Air temperatures were continuously recorded inside four incubators with proportional heating control and six incubators with on/off heating cycles, during routine use. The air temperatures in the former were constant throughout, with a gradient between the roof and above-mattress air temperature not exceeding 1 degree C. In contrast, the recordings from the latter models showed a regular cyclical oscillation, the duration of the cycle varying from 14 to 44 minutes. Each incubator had a characteristic profile. The roof air temperature could vary by as much as 7-1 degrees C and the above-mattress air temperature by as much as 2-6 degrees C during the cycle. The oscillation persisted in the air temperatures recorded inside an open-ended hemicylindrical heat shield when used inside these incubators, but was markedly reduced inside a closed-ended heat shield, Carbon dioxide concentration did not increase significantly inside the latter.